KONTRIBUSI AGROFORESTRY DALAM MENYELAMATKAN HUTAN DAN KETAHANAN PANGAN NASIONAL - J. M. Sri Hardiatmi (Innofarm:Jurnal Inovasi Pertanian, 2008)
ABSTRACT Agroforestry is the metode for the forest land management. In agroforestry the society use the land with many kind of plant like the wood forest ( Mahoni, Jati, Sengon, Suren Gaharu Dll ) and the Multi Purpose Tree Species. Within this system, the forest is planted with various kinds of crop plants such as cacao, coconut, Jack fruit, sukun, etc). Beside those trees, there can be growth also other annual trees such as polowijo, empon-empon, and horticulture). The aim of Agroforestry is to optimize the use of space horizontally and vertically, either on the soil or under the soil, so that the soil nutrient and the sunlight can be used maximally. The application of Agroforestry pattern can be done in the general forest means the forest that is built independently by the society or the forest which is built in the productive forest area. This Agroforestry pattern is designed to produce logs and other commodities which can increase the income and the welfare of the society themselves. This Agroforestry system has many advantages: (1) this system makes the soil quality fertile because of the increasing organic material. (2) Ecologically, the shading of trees gives maximum protection for the soil from the risk of erosion due to rains. (3) The society who applies the system has strong bonding psychologically with the forest so that they have fully responsibility managing the forest start from the preparation, plantation, maintenance, and harvesting. The society has strong motivation to keep the forest. The forestry department and other people who are concern towards the work of people around the forest have chosen Agroforestry activity as the main activity. By this activity, the people are expected to do productive activities within the area of the forest, so that people or society will be more well-fare. When the society is well-fare, the pressure toward the forest will be decreased. Key words: Public forest, the society around the forest, Agroforestry system.